Leprosy in a Lombard-Avar cemetery in central Italy (Campochiaro, Molise, 6th-8th century AD): ancient DNA evidence and demography - Rubini, Mauro; Zaio, Paola; Spigelman, Mark; Donoghue, Helen D. (Annals of human biology, 2017)
Background: The study of past infectious diseases increases knowledge of the presence, impact and spread of pathogens within ancient populations. Aim: Polymerase chain reaction (PCR) was used to examine bones for the presence of Mycobacterium leprae ancient DNA (aDNA) as, even when leprosy is present, bony changes are not always pathognomonic of the disease. This study also examined the demographic profile of this population and compared it with two other populations to investigate any changes in mortality trends between different infectious diseases and between the pre-antibiotic and antibiotic eras. Subjects and methods: The individuals were from a site in Central Italy (6th-8th CE) and were examined for the presence of Mycobacterium leprae aDNA. In addition, an abridged life mortality table was constructed. Results: Two individuals had typical leprosy palaeopathology, and one was positive for Mycobacterium leprae aDNA. However, the demographic profile shows a mortality curve similar to that of the standard, in contrast to a population that had been subjected to bubonic plague. Conclusions: This study shows that, in the historical population with leprosy, the risk factors for health seem to be constant and distributed across all age classes, similar to what is found today in the antibiotic era. There were no peaks of mortality equivalent to those found in fatal diseases such as the plague, probably due to the long clinical course of leprosy.